Compromised bone strength in patients with alcoholic liver cirrhosis - Jadzic, Jelena; Djonic, Danijela (Medicinski podmladak, 2020)
Osteoporosis and/or osteopenia are frequently observed complications in alcoholic liver disease patients, especially in it’s irreversible stage (alcoholic liver cirrhosis – ALC). Current literature review regarding osteoporosis incidence, increased fracture risk, bone mineral density changes, micro-structural alteration and pathogenetic mechanisms leading to ALC - induced decrease in bone quality is presented. It has been reported that osteoporosis is influencing a significant number of ALC patients, with a particular accent on the lumbar spine as most commonly affected skeletal site. Several risk factors and ethio-pathogenic mechanisms have been associated with the loss of bone mineral density in patients with ALC and other cirrhosis. Certain authors claim that the dominant mechanism in ALC-induced bone loss is a decrease in bone formation and osteoblastic function, while other results suggest increased bone remodelling as underlying cause of increased bone fragility in ALC patients. Increase bone fragility and susceptibility to osteoporotic fractures significantly affect life expectancy and quality of life in patients with ALC. Thus, osteological screening and individual fracture risk assessment are highly recommended for all patients with alcoholic liver cirrhosis.